Residential Location, Work Location, and Labor Market Outcomes of Immigrants in Israel - Buchinsky, Moshe; Gotlibovski, Chemi; Lifshitz, Osnat (Econometrica, 2014)
We develop and estimate a comprehensive dynamic programming (DP) model for the joint decisions of residential location, employment location, occupational choices, and labor market outcomes. We use data on immigrants from the former Soviet Union (FSU). We provide an extensive empirical evaluation of policies that have been designed to affect the residential and employment location decisions of the migrant population. The results shed new, and important, light on several issues regarding this group of immigrants. We find large regional differences in wages for the white-collar workers, but only little differences for the blue-collar workers. A careful examination of a number of policy measures indicate that a direct subsidy, in the form of a lump-sum transfer, is most effective in achieving the government stated goal of inducing people to reside in the northern region of the Galilee and southern region of the Negev. Other policies, such as rental and wage subsidies, can also be quite effective, but these are more difficult to administer.